Sound and Semantic Changes of Thai Loanwords in Bangkok Chaozhou - Parinyavottichai, Chanyaporn (Journal of Sinology (วารสารจีนวิทยา), 2014)
The objective of this research is to analyze the sound and semantic changes of Thai loanwords in Bangkok Chaozhou. The data was collected from bilingual ThaiChaozhou in Bangkok. The result reveals that sound change occurs in consonants, vowels, and tones. Additionally, the meanings of most Thai loans have become narrower than those of the words in the donor language.